2022
DOI: 10.3390/nu14142967
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Health to Young Adults Using Social Media: How, Where, and When?

Abstract: Communication with young adults about healthy lifestyle behaviours needs to result in improvements in dietary choices to impact the prevalence of diet-related diseases. This paper presents the health beliefs, behaviours, and communication practices in young Australian adults (n = 2019) by their pre-defined psycho-behavioural characteristics: Lifestyle Mavens, Health-Conscious, Aspirational Healthy Eaters, Balanced-All Rounders, Contemplating Another Day, or Blissfully Unconcerned. The Lifestyle Mavens and Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…In another study, health-related information seeking on social media was observed among individual segments with the "Lifestyle Mavens" and "Health-Conscious". The "Lifestyle Mavens" individuals were the most likely to create health content on social media, whereas the "Blissfully Unconcerned" individuals were the least likely to effectively engage with social media for health content [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, health-related information seeking on social media was observed among individual segments with the "Lifestyle Mavens" and "Health-Conscious". The "Lifestyle Mavens" individuals were the most likely to create health content on social media, whereas the "Blissfully Unconcerned" individuals were the least likely to effectively engage with social media for health content [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…What further prevents transferability and generalizability of findings was the lack of consensus on the use of social media, which was variably reported using data regarding the type, quality, and richness of channels investigated or the frequency of media use in Refs. [ [34] , [37] , [39] , [40] , [41] , 43 ]. The quantity of studies identified and reviewed also contribute to limited transferability and generalizability of the study findings.…”
Section: Limitations and Challengesmentioning
confidence: 99%
“…Future studies could also consider tailoring health promotion strategies to the differing psycho-behavioural characteristics of young adults to increase engagement and uptake. (39) Technology-based interventions have rapidly entered the health research setting but few studies report the unintended consequences on study implementation. In our study, many participants did not engage with the website, complete surveys or attend dietitian consultations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to successfully engage and retain young adults, the reward needs to outweigh the effort of participation. Future studies could also consider tailoring health promotion strategies to the differing psycho-behavioural characteristics of young adults to increase engagement and uptake ( 39 ) .…”
Section: Discussionmentioning
confidence: 99%